Asuhan Kebidanan Komprehensif Pada Ny.M.Umur 20 Tahun dengan Resiko Tinggi Kekurangan Energi Kronik (KEK), Letak Sungsang dan Tinggi Badan < 150 cm di Wilayah Puskesmas Bantarkawung Tahun 2023 - Ana Aryanti; Endang Susilowati; Mupliha Mupliha (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
According to the Indonesian Ministry of Health in 2020, the number of maternal mortality rates (MMR) in Indonesia is still quite high, totaling 4,627 cases of maternal death. This number shows an increase compared to 2019 of 4,221 cases of maternal death (Indonesian Health Profile, 2021). Objective: To apply the theory that has been obtained at the academy with comprehensive midwifery care for pregnant women, laboring women, postpartum women, newborns, and family planning in practice using Varney and SOAP documentation, is there a gap between theory and practice. Research method: In this study the authors used a qualitative research method with a case study approach which was carried out by examining a problem through a case consisting of a single unit. Results: At the first pregnancy obstetric care visit, there was a problem of Chronic Energy Deficiency (CHD) where LiLA was 22.5 cm and also breech location. After being given counseling about high calorie balanced nutrition there was an increase in the size of LiLA by 2, 5 cm so that the mother did not experience SEZ. In the process of childbirth was done by Sectio Caesarea. In the postpartum period there was no complication in the postpartum period. Newborn was normal, no problems. In family planning, Mrs. M chose to use a 3-year family planning implant. Conclusion: During the assistance to Mrs. M, the health problems experienced by Mrs. M, especially the incidence of SEZ in pregnant women can be resolved, and there is a gap between theory and practice related to the size of LiLA and the height of the mother.